Responsible Research and Innovation in the Strategy of the University of Lodz - Magdalena WISNIEWSKA (Communications of International Proceedings, 2023)
The article investigates whether the newly adopted strategy of the University of Lodz (Poland) stays coherent with the Responsible Research and Innovation (RRI) concept. RRI describes the contemporary approach towards university activity in the field of research and external input of the university. For the purposes of this paper, the desk method was implied. The necessary literature review is presented in the fields of university role, Responsible Research and Innovation (RRI), and necessary economic theory on the relationship between human activity and the environment. The literature research revealed that RRI concept has been an attractive field of study, although the search has not shown significant interest in the practical implementation of this concept in strategic documents adopted by higher education institutions (HEI). After all, a new paradigm becomes important when embedded in a practical dimension. This is why, the document of the exemplary university’s strategy is analyzed from the point of view of convergence with the RRI concept. In-person general text analysis for keyword density was conducted. Also, the analysis of the preface, mission, vision and strategic goals of the strategic plan was carried out. The research disclosed high convergence of the document with the RRI approach and dimensions.
Keywords: University; Research Impact; Responsible Research and Innovation (RRI)